IFN regulatory factor 3 of golden pompano and its NLS domain are involved in antibacterial innate immunity and regulate the expression of type I interferon (IFNa3) - Sun, Yun; Cao, Zhenjie; Zhang, Panpan; Wei, Caoying; Li, Jianlong; Wu, Ying; Zhou, Yongcan (Frontiers in Immunology, 2023)
The transcription factor interferon regulatory factor 3 (IRF3) plays an important role in host defence against viral infections. However, its role during bacterial infection in teleosts remains unclear. In the present study, we evaluated the antibacterial effects of Trachinotus ovatus IRF3 (TroIRF3) and how it regulates type I interferon (IFN). The results showed that TroIRF3 was constitutively expressed at high levels in the gill and liver. TroIRF3 was significantly upregulated and transferred from the cytoplasm to the nucleus after Vibrio harveyi infection. By overexpressing TroIRF3, the fish were able to inhibit the replication of V. harveyi, whereas knocking it down increased bacterial replication. Moreover, the overexpression of TroIRF3 increased type I interferon (IFNa3) production and the IFN signalling molecules. The nuclear localisation signal (NLS), which is from the 64–127 amino acids of TroIRF3, contains the basic amino acids KR74/75 and RK82/84. The results proved that NLS is required for the efficient nuclear import of TroIRF3 and that the NLS domain of TroIRF3 consists of the key amino acids KR74/75 and RK82/84. The findings also showed that NLS plays a key role in the antibacterial immunity and upregulation of TroIFNa3 induced by TroIRF3. Moreover, TroIRF3 induces TroIFNa3 promoter activity, whereas these effects are inhibited when the NLS domain is deficient. Overall, our results suggested that TroIRF3 is involved in the antibacterial immunity and regulation of type I IFN in T. ovatus and that the NLS of TroIRF3 is vital for IRF3-mediated antibacterial responses, which will aid in understanding the immune role of fish IRF3.